ANALYSIS OF INTERROGATIVE SENTENCES TRANSLATION IN ENGLISH INTO INDONESIAN ON THE SUBTITLE OF “ANT-MAN” MOVIE - Eris, Eris; Arifin, Fauji Imamul (IKIP Siliwangi, 2019)
This study is qualitative descriptive research. This study had been using data of document that is the subtitle of Ant-Man movie either in English or Indonesian which was translated by Horonis. The purpose of this research, to know the translation of interrogative sentences on the subtitle of this movie either interrogative sentences of Wh Question or Yes no Question. Technique of data collecting like watching the movie of Ant-Man, comparing the subtitle uses Aegisub software, and giving a code. Technique of data analyzing uses the method of document analyzing with domain analysis (to know data or not), and analisis taxonomy analysis (classifying the data into the kind of interrogative sentences). Had been found 188 data, Wh Question is 88 data (46.80 %) and Yes-no Question is 100 data (53.19 %). From type of Wh Question had been found type of what is 43 data (22.87%), where is 6 data (3.19%), who is 9 data (4.78%), why is 11 data (5.85%), when is 1 data (0.53%), and how is 18 data (9.57%). Then, from type of Yes-no Question had been found type of to be 27 data (14.36%), modal 15 data (7.97%), declarative 52 data (27.65%), and tag question 6 data (3.19%).